Mark Rothko - the exhibitions at Pace - Glimcher, Arne 1938-; Kertess, Klaus 1940-2016; Rosenblum, Robert 1927-2006; Lawrence, James; Stevens, Mark 1951-; Rose, Bernice 1935-2023; Sandler, Irving 1925-2018; Rice, Dan 1926-2003; O'Doherty, Brian 1928-2022 (Callaway, 2019)
The realist years /by Klaus Kertess --The surrealist years /by Robert Rosenblum --The watercolors 1941-1947 /by James Lawrence --Multifomrs /by Mark Stevens --A painter's progress /by Bernice Rose --Paintings 1948-1969 /by Irving Sandler --Dark Palette /Arne Glimcher --The 1958-1959 murals /interview by Arne Glimcher with Dan Rice --The dark paintings 1969-1970 /by Brian O'Doherty --The last paintings /by Brian O'Doherty --Bonnard-Rothko : color and light /by Bernice Rose
"With contributions by Klaus Kertess, Robert Rosenblum, James Lawrence, Mark Stevens, Bernice Rose, Irving Sandler, Dan Rice, Brian O'Doherty." -- title page
Keywords: Rothko, Mark -- 1903-1970; Glimcher, Arne -- 1938-; Pace Gallery; Rothko, Mark / 1903-1970 / Criticism and interpretation; Rothko, Mark; Pace Gallery / Exhibitions; Pace Gallery / Catalogs; Abstract expressionism / United States / Exhibitions; Painting, American / Exhibitions; Abstract expressionism; Painting, American; Criticism, interpretation, etc; Exhibition catalogs; Catalogs; United States